Predominance of influenza virus A(H3N2) 3C.2a1b and A(H1N1)pdm09 6B.1A5A genetic subclades in the WHO European Region, 2018–2019. Issue 35 (31st July 2020) - Melidou, Angeliki; Hungnes, Olav; Pereyaslov, Dmitriy; Adlhoch, Cornelia; Segaloff, Hannah; Robesyn, Emmanuel; Penttinen, Pasi; Olsen, Sonja J.; ,
Highlights: Co-circulation of different clades/subclades of influenza A viruses in 2018/2019 in the Region. Most circulating A(H1N1)pdm09 viruses (6B.1A) carried S183P in hemagglutinin. Genetically heterogeneous A(H3N2) viruses, with co-circulation of clades 3C.2a and 3C.3a. Antigenically distinct A(H3N2) clade 3C.3a viruses were increasingly detected until 02/2019 and then decreased. Co-circulation of genetically and antigenically diverse A(H3N2) strains challenges vaccine strain selection. Abstract: Background: The 2018/2019 influenza season in the WHO European Region was dominated by influenza A (H1N1)pdm09 and (H3N2) viruses, with very few influenza B viruses detected. Methods: Countries in the European Region reported virus characterization data to The European Surveillance System for weeks 40/2018 to 20/2019. These virus antigenic and genetic characterization and haemagglutinin (HA) sequence data were analysed to describe and assess circulating viruses relative to the 2018/2019 vaccine virus components for the northern hemisphere. Results: Thirty countries reported 4776 viruses characterized genetically and 3311 viruses antigenically. All genetically characterized A(H1N1)pdm09 viruses fell in subclade 6B.1A, of which 90% carried the amino acid substitution S183P in the HA gene. Antigenic data indicated that circulating A(H1N1)pdm09 viruses were similar to the 2018/2019 vaccine virus. Genetic data showed that A(H3N2) viruses mostly fell in clade 3C.2a (75%) and 90% of which were subclade 3C.2a1b. A lower proportion fell in clade 3C.3a (23%) and were antigenically distinct from the vaccine virus. All B/Victoria viruses belonged to clade 1A; 30% carried a double amino acid deletion in HA and were genetically and antigenically similar to the vaccine virus component, while 55% carried a triple amino acid deletion or no deletion in HA; these were antigenically distinct from each other and from the vaccine component. All B/Yamagata viruses belonged to clade 3 and were antigenically similar to the virus component in the quadrivalent vaccine for 2018/2019. Conclusions: A simultaneous circulation of genetically and antigenically diverse A(H3N2) and B/Victoria viruses was observed and represented a challenge to vaccine strain selection.